Phytochemical Compounds in Sea Cucumber Have the Potential to Reduce Oxidative Stress and Inflammation Due to Exercise: Systematic Review - Ayubi, Novadri; Padmasari, Dyah Fitria; Komaini, Anton; Syafawi, Atika; Ardha, Muchamad Arif Al; Dafun, Procopio B.; Ming, Jiang Wen; Lesmana, Heru Syarli; Putri, Dhea Regita Sastika (Physical Education Theory and Methodology, 2024)
Study purpose. This study aims to analyze and highlight the potential of Sea Cucumber in reducing oxidative stress and inflammation caused by exercise. Materials and methods. The study is a type of systematic review research using searches from various journal databases such as Science Direct, Pubmed and Web of Science. The inclusion criteria in this study were journals published in the last 5 years which discussed sea cucumber, oxidative stress, inflammation and exercise. Furthermore, the exclusion criteria in this research are journals that are not reputable or are not indexed by Scopus and Web of Science. A total of 1038 articles from the Science Direct, Pubmed and Web of Science databases were identified. A total of 8 articles that met the inclusion criteria were selected and analyzed for this systematic review. For standard operations, this study followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) assessment. Results. The results of this systematic review research report that the strong phenolic content found in Sea Cucumber has anti-oxidant properties which may reduce oxidative stress. Furthermore, the anti-inflammatory properties of sea cucumbers have the potential to reduce uncontrolled inflammation caused by intense exercise. Conclusions. The phenolic content in sea cucumbers has strong anti-oxidant properties in reducing oxidative stress. In addition, the anti-inflammatory properties of sea cucumbers may reduce uncontrolled inflammation caused by exercise. In this case, sea cucumbers have an anti-inflammatory effect by suppressing the secretion of pro-inflammatory cytokines. Through this systematic review, we recommend that future studies should perform clinical trials on the potential effects of sea cucumber on oxidative stress biomarkers and inflammatory biomarkers after exercise.